The Effectiveness of Using Kahoot in Basic Graphic Design Subject to Students’ Attention Levels and Learning Achievement - yope bintang anugerah; agus efendi; dwi maryono (Journal of Informatics and Vocational Education, 2019)
The research aims to (1) find out the differences on attention levels of students between using Kahoot and without using learning media in Basic Graphic Design subjects, (2) knowing the effectiveness of using Kahoot in Basic Graphic Design subjects compared to without using learning media in terms of student learning achievement, (3) knowing the level of students’ attention between using the Kahoot compared to without using learning media in Basic Graphic Design subjects. The population of this research were students of Multimedia class in SMK Negeri 3 Surakarta. The sample were from X MM 1, X MM 2, and XI MM 1. This type of research is quantitative research. This research uses the quasi-experimental design method, with pretest-posttest control design experiment. The sampling technique uses simple random sampling. Research data collection techniques use tests to determine student learning achievements before and after being given treatment, and questionnaires to determine the level of attention of students before and after being given treatment, other than that carried out observations and interviews as supporting data. The research data use test and questionnaires which were distributed to the experimental class and the control class consisted of 36 students for each class. Hypothesis testing uses an independent t-test to see the differences of attention levels between students who follow the learning process by using Kahoot and those who follow the learning process without using learning media. Then a normalized gain test was carried out to see the effectiveness of using Kahoot to improve student learning achievement. The result showed that: 1) there were differences in the attention levels between the experimental class and the control class as evidenced by the results of the t-test >Ttable 6.699 > 2.6479(70). 2) using Kahoot is effective to improve student learning achievement as evidenced by the results of the normalized gain test in experimental class which has a medium criterion of 0.60 compared to the control class which has a low criterion of 0.03.